Later prehistoric settlement in Cornwall and the Isles of Scilly : evidence from five excavations - Jones, Andy M.,; Kirkham, Graeme, (Archaeopress Archaeology, 2021)
'Later Prehistoric Settlement in Cornwall and the Isles of Scilly' reports on the excavation between 1996 and 2014 of five later prehistoric and Roman period settlements. All the sites were multi-phased, revealing similar and contrasting occupational patterns stretching from the Bronze Age into the Iron Age and beyond.